Management Seaweed Becomes Chips On The Upgrade Program Innovation Profile Pancasila Students in Class V of Moahino Elementary School - Sandra; Herlina; Arif Firmansyah (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Quality education in the 21st century is challenge we . The world of education has not quite enough big answer​ For face challenge said . Things This in accordance with 21 st Century Skills characteristics published by 21 Century Skills Partnership, which states that students in the 21st century must capable develop skills competitive skills needed in the 21st century which are related with Developmental Skills of the 21 st Century as : think critical (critical thinking); solving problem solving; skills communication skills, ICT skills , Information and Communication Technology (ICT), information and media literacy . Formulation problem study How Strengthening Profile Pancasila Students on Students Class V of Moahino Elementary School through Management Seaweed Becomes​ Chips . As for the purpose study This is For know How Strengthening Profile Pancasila Students to Students Class V of Moahino Elementary School through Management Seaweed Becomes​ Chips . Research methods Study This done For describe How implementation project strengthening profile Pancasila students in management grass sea at SDN Moahino . Research objectives qualitative is For understand the phenomenon being faced subject research . Research results There is results observation student served data description from each and every grain existing questions​ in sheet observation student For measure success student in manage grass sea become chips in class V SDN Moahino . There are 8 pieces indicators that must be observed during the process of implementing P5 in manage grass sea become chips given by 10 respondents . Conclusion of the study Based on results study from meeting I where student Not yet understand steps in its management finally at the second meeting of students Already Can manage , cook , to packing product chips from grass sea become chips so management grass sea become chips for students Class V of Moahino Elementary School Already succeed .